Estimating trade flows between Portuguese regions using an Input-output approach - Ana Lúcia Marto Sargento; Pedro Miguel Nogueira Ramos (European Regional Science Association (ERSA), 2003)
The paper we intend to present aims to estimate the trade flows existing between the seven Portuguese regions, considering 49 distinct commodities. This estimation is based on the construction of a multi-regional model that requires the elaboration of an Input-Output table for each one of the regions. These tables were achieved by using non-survey methods, having the Portuguese table as a starting point. However, it was possible to work, on a great part of the estimation procedure, with a considerable high level of detail: 291 commodities and 276 industries. The first proxy to the trade flows was obtained considering that the interregional net exports corresponded to the difference between total resources (supply) and total employment (demand) of the 49 commodities. These values were then modified in order to consider the existence of crosshauling. Finally, gravitational models were used to get to the final values of the trade flows between the seven regions.
Keywords: 330